The Relationship between Learning Motivation and Emotional Intelligence with Physics Learning Achievement of Public High School Students Class XI MIA in Singaraja City - Putu Ratni Ayu Utami; I Wayan Santyasa; Ni Ketut Rapi (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
This research aimed to analyzing the relationship between learning motivation and physics learning achievement, emotional intelligence and physics learning achievement, and learning motivation and emotional intelligence with physics learning achievement at SMA Negeri in Singaraja city. The type of this research was ex-post facto with correlation quantitative method. The result of this research was the students’ physics learning achievement which is low and it shows that there are the positive relationship between learning motivation and emotional intelligence with physics learning achievement.